2020
DOI: 10.1186/s12199-020-00870-9
|View full text |Cite
|
Sign up to set email alerts
|

Health impacts of environmental contamination of micro- and nanoplastics: a review

Abstract: Plastics are extensively used in our daily life. However, a significant amount of plastic waste is discharged to the environment directly or via improper reuse or recycling. Degradation of plastic waste generates micro-or nanosized plastic particles that are defined as micro-or nanoplastics (MNPs). Microplastics (MPs) are plastic particles with a diameter less than 5 mm, while nanoplastics (NPs) range in diameter from 1 to 100 or 1000 nm. In the current review, we first briefly summarized the environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(106 citation statements)
references
References 124 publications
(209 reference statements)
0
85
0
2
Order By: Relevance
“…In addition, it is necessary the effect of residual plastic particles, which are smaller and more contaminated in chemical substances and therefore can cause nanoscale toxicity (Jiang et al 2020).…”
Section: Biodegradation Of Plastic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is necessary the effect of residual plastic particles, which are smaller and more contaminated in chemical substances and therefore can cause nanoscale toxicity (Jiang et al 2020).…”
Section: Biodegradation Of Plastic Wastementioning
confidence: 99%
“…Currently, only the HBCD additive was investigated by Brandon et al (2020) in PS-degrading larvae and further up the food chain in TM-fed shrimp. Then, further studies are needed to evaluate the presence of several plastic-derived substances able to cause different toxic effects (Jiang et al 2020). Consequently, lots of fundamental research remains to be done, also to fill current regulatory gaps.…”
Section: Critical Aspects Of Plastic Biodegradation and Pha Recovery Through Tmmentioning
confidence: 99%
“…Recent studies have found MPs in human stool samples, which also indicate that humans are exposed to MPs through food and beverages (Jiang et al., 2020; Schwabl et al., 2019). Mohamed Nor et al.…”
Section: Bioavailability Of Mps By Humanmentioning
confidence: 98%
“…Although these studies show that human body can digest and eliminate these particles, the toxic effects of MPs on tissues and organs during the circulation and accumulation in the body cannot be ignored. In addition to MPs themselves, these tiny plastic particles can also release plastic additives and toxic chemicals adsorbed from the environment, many of which have been proven to be endocrine disruptors (Jiang et al., 2020).…”
Section: Bioavailability Of Mps By Humanmentioning
confidence: 99%
“…Under environmental conditions, plastic waste slowly degrade due to chemical, mechanical, and biological actions into micrometric and submicrometric plastic particles (Andrady, 2015;Frias and Nash, 2019). The smaller they are, the easier they can be ingested, accumulated and transferred by organisms along the food chain (Jiang et al, 2020). Ingestion of micrometric and submicrometric plastics is known to cause direct adverse effects (e.g., entanglement, suffocation) and to expose organisms to plastic-associated chemical and microbial agents with a prominent toxic and pathogenic potential (Sathicq et al, 2021;Vethaak and Leslie, 2016;Zhang and Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%